Pendidikan Karakter Pada Anak Sekolah Dasar Di Era Digital - Erwin Elihut Upu; Maria Helmiana Ghele; Thomas Kemil Masi (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
Character education is a process of applying moral and religious values to students through the acquisition of knowledge. Its purpose is to shape individuals with good personalities, responsibility, empathy, integrity, and the ability to contribute positively to society. The application of these values extends to oneself, family, friends, educators, the surrounding environment, and the Divine. The social development of elementary school-age children has expanded, starting from interactions primarily within the family and gradually branching out to acquaintances in the immediate surroundings. Children of this age have also become acquainted with the digital lifestyle, whether from home, friends, school, or the environment. The digital era has brought not only positive impacts but also negative ones. This is where our role as parents, educators, and responsible adults comes in – to guide and supervise children in navigating it in a beneficial, appropriate, and positive manner for their well-being.